PENGARUH PENERAPAN I.S.O 9001:2000, KUALITAS PRODUK DAN LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK GENTENG PT.PRIMA MANUNGGAL INTI INTERNUSA - Zahrida Z Wiryawan (Jurnal Manajemen., 2011)
The present changes from oligopolistic markets into perfectly competitivemarket brings effects where customers now demand more for standardized qualityofferings. Marketers are therefore obliged that the quality of their offerings areconsistent with the promised specification level. In compliance with this, P.T PrimaManuggal Inti Internusa has decided to implement the ISO 9001 :2000 managementsystem for its roof products, while maintainenace of the delivered quality should be inaccordance with the companys standard through the documentation of every relatedprocess, so that all personnel perform their works with similar pattern systematically asrequired by the approved ISO procedure.Ever since the ISO started to be implemented, there has been a 18% increase in sales ofits roof products for the year 2008, and another 7% increase for the year 2009.Although it may mean that there were significant increases for the firms productsduring those two consequtive years, there has not yet been any investigation carried onthe variables which were the determinants for these increases as well as the level ofthese variables as influencers of the increasesThis research attempted to investigate which variables had been the determinants: ISO9001 :2000, quality of product and quality of service; as influencers of the customerspurchasing decisions of the roof products.Using a quantitative design with 113 respondents, the f test and t test indicated thatthe implementation of the ISO 9001:2000, quality of the products as well the quality ofits services did simultaneously and partially influence customers purchasing decision ofthe companys roof products positively.